Using Animal Models to Disentangle the Role of Genetic, Epigenetic, and Environmental Influences on Behavioral Outcomes Associated with Maternal Anxiety and Depression - Tarantino, Lisa M.; Sullivan, Patrick F.; Meltzer-Brody, Samantha (Frontiers in Psychiatry, 2011)
The etiology of complex psychiatric disorders results from both genetics and the environment. No definitive environmental factor has been implicated, but studies suggest that deficits in maternal care and bonding may be an important contributing factor in the development of anxiety and depression. Perinatal mood disorders such as postpartum depression (PPD) occur in approximately 10% of pregnant women and can result in detriments in infant care and bonding. The consequences of impaired maternal-infant attachment during critical early brain development may lead to adverse effects on socioemotional and neurocognitive development in infants resulting in long-term behavioral and emotional problems, including increased vulnerability for mental illness. The exact mechanisms by which environmental stressors such as poor maternal care increase the risk for psychiatric disorders are not known and studies in humans have proven challenging. Two inbred mouse strains may prove useful for studying the interaction between maternal care and mood disorders. BALB/c (BALB) mice are considered an anxious strain in comparison to C57BL/6 (B6) mice in behavioral models of anxiety. These strain differences are most often attributed to genetics but may also be due to environment and gene by environment interactions. For example, BALB mice are described as poor mothers and B6 mice as good mothers and mothering behavior in rodents has been reported to affect both anxiety and stress behaviors in offspring. Changes in gene methylation patterns in response to maternal care have also been reported, providing evidence for epigenetic mechanisms. Characterization of these two mouse inbred strains over the course of pregnancy and in the postpartum period for behavioral and neuroendocrine changes may provide useful information by which to inform human studies, leading to advances in our understanding of the etiology of anxiety and depression and the role of genetics and the environment.